Concepção de professores e alunos sobre sexualidade, gênero e diversidade sexual: estudo de caso no Colégio Estadual Prof. Antônio Março de Araújo (Luziânia/GO) - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The school as an instrument of reproduction of the ideology of the dominant class replicates for students the standards and norms established by it, that is, the school environment often absorbs and disseminates the social and cultural aspects practiced in society, among which we highlight discrimination. , the non-acceptance, disrespect and exclusion of LGBTQIA+ people, evidence that aroused our interest in carrying out this research, as we understand that despite resistance and discrimination within the school and the classroom there are numerous possibilities for discussions, dissemination of information and clarification on sexuality, gender and sexual diversity. In our view, society involves and is involved by various diversities and adversities, in which different people, cultures, habits, customs, sexualities, among other aspects, are contained. In this context, we believe that it is necessary to understand and, above all, respect this dynamic reality of which we are a part. In the expectation of directing the research, we established as a central objective to analyze the understanding that teachers and students of the 3rd year of High School at Colégio Estadual Professor Antônio Março de Araújo (Luziânia/GO) present about sexuality, gender and sexual diversity and how such issues are worked on. Inside the classroom. To undertake the research, we chose to use the “case study”, as it represents an empirical method of investigating contemporary phenomena in their depth and in their real-world contexts, especially when the boundaries between the phenomenon and the context are not clearly evidenced. Regarding the analysis of the collected data, we used a quantitative-qualitative approach, since it allows us to carry out a holistic characterization of a phenomenon that materializes in a natural situation, full of descriptive information, it has an open, flexible and focused plan complexity and contextualization of reality. Therefore, it constitutes an instrument of substantial potential for us to have the conditions to know and understand the contexts that characterize the interactions and actions within the school. Our findings indicate that there is an urgent need for the school to expand its action and performance to fulfill its social responsibilities – while considering the competences and responsibilities of the State established in Brazilian legislation –, by understanding and adapting to the permanent process of transforming society towards the establishment of a respectful and friendly coexistence with human diversities
Teachers' and students' conception of sexuality, gender and sexual diversity: case study at Colégio Estadual Prof. Antônio March de Araújo (Luziania/GO)
Keywords: Educação - Sexualidade; Escola - Discriminação Sexual; Identidade de Gênero - Luziânia/GO; Education and Sexuality; School and Sexual Discrimination; Gender Identity in Luziânia/GO; CIENCIAS HUMANAS::EDUCACAO